2016
DOI: 10.11648/j.ajep.20160501.11
|View full text |Cite
|
Sign up to set email alerts
|

Land Use and Land Cover Change in a Community-Managed Forest in South-Eastern Senegal Under a Formal Forest Management Regime

Abstract: While most studies of community forests in Senegal address issues in institutional and political arrangements for managing forests, this study was carried out to find out how these political and institutional changes embodied in the new approach to forest management impact on land use and land cover change in the country. Using the Missirah Forest in southeastern Senegal, as a case study, the objective was to quantify the land use and land cover changes that have happened over a twenty four-year period, from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Different researchers use different system to collect reference data, also called ground truth. For instance, ground observation using GPS (Faye et al, 2016;Hailemariam et al, 2016;Park, 2016), aerial photography (Hailemariam et al, 2016), available thematic maps interpretation (Ghosh & Das, 2019;Sarkar, 2018) and Google earth images (Alqurashi &Kumar, 2013;Bisrat & Gizaw, 2018;Herold et al, 2002) can be used. The most common sampling system that is used for collecting reference data is simple random sampling, systematic sampling, stratified random sampling, cluster sampling, and stratified systematic (Padmanaban et al, 2017).…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…Different researchers use different system to collect reference data, also called ground truth. For instance, ground observation using GPS (Faye et al, 2016;Hailemariam et al, 2016;Park, 2016), aerial photography (Hailemariam et al, 2016), available thematic maps interpretation (Ghosh & Das, 2019;Sarkar, 2018) and Google earth images (Alqurashi &Kumar, 2013;Bisrat & Gizaw, 2018;Herold et al, 2002) can be used. The most common sampling system that is used for collecting reference data is simple random sampling, systematic sampling, stratified random sampling, cluster sampling, and stratified systematic (Padmanaban et al, 2017).…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…Similar patterns of land use trend over the time were described in other West African countries. These include studies in southern Burkina Faso (Ouedraogo et al, 2010), western Senegal, (Sambou et al, 2015) and south-eastern Senegal (Faye et al, 2016). A study carried out by USGS (USGS, 2016b) in a 38-year period (1975 to 2013) showed that the fastest average annual rate of cropland expansion in West Africa were found in Togo, Benin, Chad, Mauritania and Burkina Faso and in every country of the same region, agriculture was exerting pressure on the natural landscapes, replacing fragmented savanna, woodland and forests.…”
Section: Land Use Land Cover Changes In the Overall Acm From 1987 To mentioning
confidence: 99%